Evolution of social food assistance programs in Mexico through Ensanut MC 2016 data - M del Carmen Morales-Ruán; Teresa Shamah-Levy; Verónica Mundo-Rosas; Lucía Cuevas-Nasu; Ana Lilia Lozada-Tequeanes; Martín Romero-Martínez (Instituto Nacional de Salud Pública, 2018)
Objective. To describe the coverage and targeting of Social Food Assistance Programs (SFAP) in Mexico. Materials and methods. Data were obtained from 9 137 households of the Halfway National Health and Nutrition Survey 2016 (Ensanut MC 2016) who receive SFAP. The distribution of the SFAP by place of residence, index of socioeconomic status and SFAP relevance were analyzed. Results. 44% of households receive some SFAP, with a higher concentration in indigenous households (70%), a very low socioeconomic level (70%), and moderate and severe food insecurity. The SFAP with the greatest coverage were Prospera (21%), Liconsa (9%), School Breakfasts Program (17%) and the Support Program for Older Adults; of these the best-focused program was Prospera. Conclusions. It is necessary to review the resources of the programs and direct them to the population with greater deficiencies and greater nutritional vulnerability.